Sustainable Liquid-Phase Selective Hydrogenation of CO2 to C1–C3 Alcohols over Mg-, Zn-, and Pt-Modified Copper Phyllosilicate Catalysts: Insight Reaction Pathways - Poson, Suttiporn; Teerawatananond, Thapong; Shoosri, Tanyarat; Miyake, Takanori; Panpranot, Joongjai; Weerachawanasak, Patcharaporn (My University, 2026)
The sustainable conversion of carbon dioxide (CO2)into value-added chemicals remains a major challenge, particularly for the selective formation of C1–C3 alcohols. Herein, bimetallic copper phyllosilicate catalysts (1%X-20%CuPS, X = Zn, Mg, Pt) were developed and systematically evaluated for the liquid-phase hydrogenation of CO2 to alcohols compared with monometallic 20%CuPS as a benchmark. Among these catalysts, 1%Mg-20%CuPS exhibited the highest activity, excellent stability, and good reusability, highlighting the beneficial role of earth-abundant metal promotion. The enhanced performance is attributed to increased surface basicity and stronger CO2 adsorption, which facilitated the formation and stabilization of formate intermediates. Concurrently, in situ reduction of Cu+/Cu0 sites promotes efficient H2 dissociation and subsequent hydrogenation steps. A high surface Mg/Si ratio further stabilizes CO-derived intermediates and promotes CO-mediated C–C coupling, favoring C2+ alcohol formation. Zn incorporation induced similar but less pronounced effects, whereas Pt altered the reaction network, leading to increased byproduct formation and lower alcohol selectivity. After 24 h, the total alcohol selectivity followed the order 1%Mg-20%CuPS (98%) > 1%Zn-20%CuPS (88%) > 1%Pt-20%CuPS (73%) > 20%CuPS (67%). Overall, second metal modification effectively tunes catalyst properties and reaction pathways, with Mg emerging as a sustainable and industrially viable promoter for CO2 valorization to C1–C3 alcohols.
Keywords: C1–C3alcohols; carbon dioxide; copper phyllosilicate; hydrogenation; liquid-phase; magnesium